Análisis de la información y contenido de las plataformas digitales de la unidad educativa pio Jaramillo Alvarado, para el mejoramiento de la gestión de la comunicación institucional interna y externa, período noviembre 2016-marzo 2017 - Puglla Yangari, Fanny Lucia (2017)
The present investigation titled “ANALYSIS OF THE INFORMATION AND CONTENT OF THE DIGITAL PLATFORMS OF THE EDUCATIONAL UNIT PIO JARAMILLO ALVARADO, FOR THE IMPROVEMENT OF THE MANAGEMENT OF INTERNAL AND EXTERNAL INSTITUTIONAL COMMUNICATION, PERIOD NOVEMBER 2016- MARCH 2017”, Has as purpose analyze the treatment of Information and content of the digital platforms of the Educational Unit Pio Jaramillo Alvarado. To carry out the research the scientific method was used with a quantitative-qualitative approach and the tools and instruments that were used were Recognition and identification table, semistructured interview, content analysis, bibliographic review and surveys, which allowed analyzing the bankruptcies that the institution has in the management of communication, through its digital platforms. The results of the research show that the educational institution under study has poor communication management in the web.